ISSUES CONCERNING PROTECTION OF THE VINE FAMILY (FAMILY VITACEAE JUSS.) IN THE RUSSIAN FAR EAST - N. I. Denisov (Труды по прикладной ботанике, генетике и селекции, 2018)
Analyzing classification features of vines of the family Vitaceae Juss. in the Russian Far East (RFE) confirms the need for their protection within the region. Protection should be extended to species of the rarity categories 1, 2 and 3. For the RFE (as a whole) these are the species: Ampelopsis japonica (Thunb.) Makino, Parthenocissus tricuspidata (Siebold & Zucc.) Planch. - 1; Ampelopsis heterophylla (Thunb.) Siebold & Zucc. - 2; Ampelopsis brevipedunculata (Maxim.) Trautv., Vitis coignetiae Pulliat ex Planch. - 3; and Vitis amurensis Rupr. - 4. Our field studies in the territory of the Russian Far East have allowed us to assess the condition of a number of woody vines in natural habitats, clarify the distribution and propose measures for conservation of their gene pool. It is recommended to supplement the list of nature reserves and sanctuaries with a number of areas where woody vines occur.